Measuring Belief in Climate Change With a Single Item - Sebastian Berger; David Hauser; Anna Lange; Sander van der Linden (Global Environmental Psychology)
Brief, but psychometrically valid assessments of psychological constructs are increasingly needed to be included in larger psychological and other social scientific studies, such as Many Labs projects or representative surveys. Here, we provide a novel one-item measure of individual differences in belief in climate change. Based on two studies (N = 913, N = 288) recruited from various global regions, we establish convergent, predictive, and discriminant validity. More specifically, we find that the single-item measure correlates with other constructs measuring belief in climate change and with relevant downstream constructs, among them intentions to engage in pro-environmental behavior, actual consequential behavior, and self-reported everyday behaviors. We therefore conclude that the single item is a suitable instrument to measure belief in climate change when multiple-item assessments are either too costly or otherwise unfeasible.